The role of entertainment media in perceptions of police use of force - Donovan, Kathleen M. (Criminal justice and behavior, 2015)
Scholars have long noted the importance of the media in shaping citizens? attitudes about crime and justice. Most studies have focused on the impact of news and particularly local TV news, yet Americans spend far more time watching entertainment media. We examine the portrayal of police misconduct in crime dramas, and how exposure to these portrayals affects perceptions of the police. We find that viewers of crime dramas are more likely to believe the police are successful at lowering crime, use force only when necessary, and that misconduct does not typically lead to false confessions. In contrast, perceptions regarding the frequency of force are unaffected. Our results add to a growing literature demonstrating the importance of entertainment media for attitudes toward crime and the criminal justice system.